Innovative Art-Supported Techniques for Teaching English to Primary School Students - Subanova Dilafruz Vahapjanovna (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
The article examines innovative technologies for teaching English to young learners through the integration of art-based methods, with a particular emphasis on drama and its related forms - such as simulation, role-play, puppetry, and pantomime. These interactive and expressive techniques are explored as effective tools for enhancing communicative competence, emotional intelligence, and cultural awareness among young learners. The study discusses how drama-based technologies foster creativity, motivation, and linguistic confidence by engaging children in authentic communicative situations. It also analyzes the methodological and psychological foundations of incorporating drama into the English language classroom, demonstrating that art-infused instruction-supported by modern digital tools - creates a multisensory and learner-centered environment conducive to holistic language development.